Beam Tracking Aided by Complexity-Reduced MobileNetV2 for Water-Air OWC With Waves - Xu, Anzi; Di, Yujie; Yue, Xiangyu; Chen, Lian-Kuan (IEEE photonics technology letters, 2024)
Wave-induced beam wander degrades communication performance, which causes a high bit error rate (BER) and packet loss rate (PLR) in water-air OWC. We propose and experimentally demonstrate a real-time beam tracking system utilizing an image pre-processing algorithm and a MobileNetV2-based model to mitigate wave-induced effects in water-air OWC. The tracking system is optimized and compared with the ResNet-based tracking system in terms of tracking and communication performance. For non-tracking cases, the PLR is significantly higher, with values exceeding 20%. With a 1.3-m air path, a zero-packet-loss link is realized by the MobileNetV2-based tracking method at a data rate of 800 Mbit/s and a wave average slope changing rate (ASCR) of 28 deg/sec.